O sertão inventado: a percepção dos sertões maranhenses pelo olhar de Francisco de Paula Ribeiro - dos Santos, Raimundo Lima (Diálogos Latinoamericanos, 2012)
This text mentions the construction of a look at the sertões Maranhão, established by the Portuguese military Francisco de Paula Ribeiro on the threshold of the nineteenth century. Cutting the work done in Portuguese, the installation of Royal Farms and demarcation of the borderline between the captaincies Maranhão and Goiás, Paula Ribeiro traveled throughout the hinterland and reported through his memoirs written, geographical aspects, economic and cultural region. This set of prints made during the first two decades of the century, is here cognominado of "creating perceptions." Are creating at the time the main intellectuals who wrote about the sertões in the first half of the twentieth century kept part of the impressions ribeirianas, corroborating to fix images in the recovery geographical, demonstration of abandonment and loss of indigenous human element in favor of cattlemen.